Postpyloric feeding tube placement at the bedside: Complication rate and impact on length of stay. (10th July 2021) - Gillis, Holly Catherine; Lin, Ada; Jackson, Kenneth; Stewart, Claire
Abstract: Background: Postpyloric feeding tube (PPFT) placement is essential for the ongoing nutrition care of critically ill children requiring noninvasive and invasive ventilation. PPFTs are placed by a variety of providers, including advanced practice nurses (APNs), surgeons, gastroenterologists, and radiologists. Complication rates, time to enteral nutrition (EN) following placement, and association with length of stay (LOS) have not been well documented. Methods: A query of the electronic medical record identified patients in the pediatric intensive care unit (PICU) in whom PPFTs were placed. A retrospective chart review was performed to identify patient demographics; PPFT placement provider, indication, and duration; PICU LOS; hospital LOS; and patient pediatric risk of mortality (PRISM) scores. Results: A total of 452 PPFTs were placed in 346 patients, with 318 placed by APNs. There was only one complication in 452 placed PPFTs. PRISM scores between patient groups for APN‐placed PPFTs and non‐APN–placed PPFTs were not significantly different. Mean time from hospital admission to PPFT placement was 1.5 days (APN) to 2.0 days (non‐APN) ( P < .02). Spearman correlation coefficients demonstrated shorter hospital and PICU LOS were associated with shorter duration to insertion. Conclusion: Overall complication rates of PPFT insertion is very low and do not significantly differ between provider type, even in patients with higher PRISM scores. Additionally, early time to insertion of PPFT is associated with decreased hospital and PICU LOS. Further research is needed to determine if the earlier time to insertion of PPFTs is associated with the achievement of goal feeds.